Cultivation Of Religious Character Values Through Getting The Habit Of Dhuha Prayer Activities In Children Aged 5-6 Years At Permata Hati Kindergarten-Centerislamic Preschoolmataram - Baiq Parida Aulia Nur Hawani; Wahyu Hananingsih; Nur Kholidah Nasution (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Instilling religious character values through the habituation of Dhuha prayer activities in children aged 5-6 years at Permata Hati Kindergarten, Islamic Preschool, Mataram. Dhuha prayer was chosen as a medium because it is believed to develop spiritual values, discipline, responsibility, and obedience in early childhood. This study uses a descriptive qualitative approach with a field research type. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data analysis used an interactive model that includes data reduction, data presentation, and conclusion. Data validity was assessed through diligent observation, source triangulation, technical triangulation, and the adequacy of references. The results of the study indicate that: (1) the instillation of religious character values is carried out through three main strategies, namely: (a) religious education is not only delivered formally but through habituation; (b) providing opportunities for students to express themselves through demonstrations and exercises; (c) creating a religious situation by explaining commands and prohibitions as well as rewards and punishments in a simple manner. (2) The religious character of children that is formed includes: believing in and obeying God, discipline, patience, self-confidence and independence, and honesty, which is reflected in daily behavior. (3) Supporting factors include parental support and adequate facilities, while inhibiting factors are schedule conflicts with extracurricular activities. outing class, and meetings that use the hall.